2022
DOI: 10.3390/cancers14184360
|View full text |Cite
|
Sign up to set email alerts
|

Oncologic Benefits of Neoadjuvant Treatment versus Upfront Surgery in Borderline Resectable Pancreatic Cancer: A Systematic Review and Meta-Analysis

Abstract: Neoadjuvant treatment (NAT) followed by surgery is the primary treatment for borderline resectable pancreatic cancer (BRPC). However, there is limited high-level evidence supporting the efficacy of NAT in BRPC. PubMed was searched to identify studies that compared the survival between BRPC patients who underwent NAT and those who underwent upfront surgery (UFS). The overall survival (OS) was compared using intention-to-treat (ITT) analysis. A total of 1204 publications were identified, and 19 publications with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 40 publications
(154 reference statements)
0
7
0
Order By: Relevance
“…These results have been further corroborated by several cohort studies, matched-propensity analyses, systematic reviews, and meta-analyses comparing neoadjuvant therapy approaches to up-front surgical approaches, although the studies are limited due to variability in definitions of resectability and treatment regimens 38,41–61 . A meta-analysis of 27 studies and 63,151 patients, including 8461 who received neoadjuvant chemotherapy and 54,690 patients who received up-front surgery, demonstrated that neoadjuvant chemotherapy resulted in a better OS (hazard ratio [HR]: 0.72, 95% CI: 0.69-0.76) and improved R0 resection rate (HR: 0.62, 95% CI: 0.60-0.65) compared with up-front surgery 41 …”
Section: Summary Of Literature Reviewmentioning
confidence: 83%
“…These results have been further corroborated by several cohort studies, matched-propensity analyses, systematic reviews, and meta-analyses comparing neoadjuvant therapy approaches to up-front surgical approaches, although the studies are limited due to variability in definitions of resectability and treatment regimens 38,41–61 . A meta-analysis of 27 studies and 63,151 patients, including 8461 who received neoadjuvant chemotherapy and 54,690 patients who received up-front surgery, demonstrated that neoadjuvant chemotherapy resulted in a better OS (hazard ratio [HR]: 0.72, 95% CI: 0.69-0.76) and improved R0 resection rate (HR: 0.62, 95% CI: 0.60-0.65) compared with up-front surgery 41 …”
Section: Summary Of Literature Reviewmentioning
confidence: 83%
“…Nevertheless, chemotherapy resistance and adverse effects of the anti-cancer drugs may make some patients miss the opportunity of surgery. Studies reported that the overall resection rate was lower in NAT group than upfront surgery group [ 7 , 8 ]. Reliable diagnostic methods are urgently needed to accurately predict the tumor response, as well as to optimal therapeutic selection in patients that are suitable for NAC.…”
Section: Discussionmentioning
confidence: 99%
“…Inadequate tumor response may facilitate tumor progression, obviating the opportunity to completely resect the tumor [ 2 , 6 ]. Several meta-analyses have reported the resection rate was lower in neoadjuvant therapy (NAT) group than upfront surgery group [ 7 , 8 ]. Jung et al [ 7 ] thought that lacking reliable criteria to select patients who are suitable to undergo surgical resection and the low rate to complete chemotherapy cycles due to various adverse effects from anti-cancer agents may be associated with the above results.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the Authors, NAT is associated with a longer survival for patients with BRPC, but its broader efficacy in cases of resectable PDAC, and the optimal treatment strategy have yet to be established. In borderline resectable-locally advanced PDAC (BR/LAPC) patients NAT reportedly significantly increases the resection rate, the R0 resection rate, the node-negativity rate, and the median DFS and OS, 12 , 103 - 105 making it the treatment of choice for these patients.…”
Section: Role Of Nat In the Surgical Treatment Of Pdacmentioning
confidence: 99%